Ethnic disparities in patients with early-onset Alzheimer’s disease (EOAD) - Yang, Meredith; Yoon, Suemin Jasmine; Taruc, Kristen; Timpo, Phyllis; Mastrianni, James; Seibert, Kaitlin (Frontiers in Neurology, 2025)
IntroductionEthnic disparities in Early-onset Alzheimer’s Disease (EOAD) have not been fully characterized.MethodsWe retrospectively identified 81 EOAD patients February 2017–February 2022.Results53 (65.4%) identified as White and 28 (34.6%) identified as Black. Age at diagnosis (years) was (57.3 ± 5.24) in Black patients compared to (56.3 ± 4.96) in White patients. Time to diagnosis (years) was longer in Black patients (3.39 ± 1.85) compared with White patients (2.64 ± 1.75). Black patients had lower MOCA scores (12.17 ± 6.9) compared with White patients (14.9 ± 5.8). An amnestic profile was more common in Black patients (19 or 67.9%) than non-amnestic presentations (9 or 32.1%). Non-amnestic presentations were more common in White patients, with 9 (17%) patients with PCA, 8 (15%) with fAD and 8 (15%) with l-PPA.DiscussionIn our cohort, Black patients with EOAD are on average older, more advanced and experienced longer delays in diagnosis than their White counterparts.